Assault-related facial fractures: does the injury mechanism matter? - Arpalahti Annamari; Haapanen Aleksi; Puolakkainen Tero; Abio Anne; Thorén Hanna; Snäll Johanna (Elsevier, 2022)
Abstract
This study clarified the injury characteristics and occurrence of associated injuries in patients with assault-related facial fractures. Data from 840 assault-related facial fracture patients were included; demographic factors, facial fracture type, associated injuries, alcohol use, and injury mechanisms were recorded. Assault mechanisms most often included combinations of different mechanisms (57.5%) and resulted in the victim falling (50.1%). The perpetrator was most commonly a stranger (52.5%) and acted alone (57.7%). A total of 123 patients (14.6%) had associated injuries, with the most common being traumatic brain injury. Associated injuries occurred most frequently in patients with combined fractures of the facial thirds (24.2%) and upper third fractures (42.9%). The most significant differentiating factors for associated injuries were the number of perpetrators, falling, the use of an offensive weapon, and if the events of the assault remained unknown. In adjusted logistic regression analyses, statistically significant associations with associated injuries were found for age (odds ratio (OR) 1.05, 95% confidence interval (CI) 1.03–1.07; P < 0.001), falling due to the assault (OR 2.87, 95% CI 1.49–5.50; P = 0.002), and upper third facial fractures (OR 6.93, 95% CI 2.06–23.33; P = 0.002). A single punch also caused severe injuries and should therefore not be overlooked, as this can be as dangerous as other assault mechanisms.